MINIMUM WAGE FOR WORKERS IN MICRO AND SMALL ENTERPRISES: ANALYSIS OF GOVERNMENT REGULATION NUMBER 36 OF 2021 - I Wayan Bagus Pramana; I Gede Yusa (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This study aims to explore legal views on the implementation of wages below the minimum wage for Micro, Small Enterprises (MSEs) in Indonesia. The research method applied is a literature study that includes an analysis of Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law, Government Regulation Number 36 of 2021 on Wages, as well as related case studies in the field. The results show that wage arrangements for MSEs aim to protect workers' welfare and improve decent living standards. Nevertheless, its implementation faces various challenges, especially in terms of law enforcement against employers who do not comply with the stipulated minimum wage provisions. This shows that there is an expansion of the reach of legal protection for workers/laborers in the MSEs sector.